Material Decomposition in Dual-Energy Computed Tomography Separates High-Z Elements From Iodine, Identifying Potential Contrast Media Tailored for Dual Contrast Medium Examinations. Issue 6 (November 2015) - Fält, Tobias; Söderberg, Marcus; Wassélius, Johan; Leander, Peter
Abstract : Objective: The aim of this study was to determine the potential of different high-Z elements to act as contrast media (CMs) alongside iodine (I) in dual-CM, dual-energy (DE) computed tomography examinations. Methods: Gadolinium (Gd), tantalum (Ta), wolfram (W), gold (Au), and bismuth (Bi) in addition to I were examined at all available kilovolt settings in a DE computed tomography scanner. Dual-energy ratios were calculated by dividing attenuation at low kilovolt by attenuation at high kilovolt. Dual-energy data sets were loaded into material decomposition software to evaluate separation of the elements from I. Results: The DE ratios of Ta, W, and Au ranged between 0.9 and 1.2, being considerably lower than I at 1.9 to 2.6. These elements were completely separated from I using material decomposition. Gadolinium and Bi were more similar to I at 1.4 to 1.9. However, separation was nearly complete for Bi and suboptimal for Gd. Conclusions: Tantalum, W, and Au are ideal candidates for dual-CM examinations, whereas Bi is a slightly weaker candidate.